Makers of Modern Strategy : From Machiavelli To The Nuclear Age - Edited By Paret, Peter and With The Collaboration of Craig, Gordon A. and Gilbert, Felix (New York Oxford University Press, 2010)
War cannot be controlled in future without an understanding of its past. These essays analyse war, its strategic characteristics and its political and social functions, over the past five centuries.
Includes Bibliographical Notes and Index.
Keywords: Strategy -- Military Art and Science